2022
DOI: 10.31460/mbdd.1066621
|View full text |Cite
|
Sign up to set email alerts
|

Accounting of Crypto Assets

Abstract: After the introduction of Bitcoin in 2008, many new concepts such as crypto currency, crypto assets, tokens, distributed ledger, blockchain, smart contracts, decentralized applications have taken place in our language. Technological developments have also affected the economic assets of the enterprises. These assets are bought and sold in the market, traded and reach monetary sizes in large amounts. While businesses are building a business model on new generation technological assets, it is inevitable that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The issue of how crypto assets should be accounted according to international accounting/financial reporting standards has been examined by scanning world-wide practices, and it is aimed to create an infrastructure for a legislative study to be carried out in the field of accounting in each country (Alici & Yanik, 2022). Further, Pramana et al (2023) conducted a study of accounting for Crypto-asset based on the applicable IAS and found that the most common treatment for Crypto asset is as Intangible Asset and Inventory since the used of Crypto-Asset until now mostly as investment and trading in contract futures.…”
Section: Audit Of Crypto Currency Transactionsmentioning
confidence: 99%
“…The issue of how crypto assets should be accounted according to international accounting/financial reporting standards has been examined by scanning world-wide practices, and it is aimed to create an infrastructure for a legislative study to be carried out in the field of accounting in each country (Alici & Yanik, 2022). Further, Pramana et al (2023) conducted a study of accounting for Crypto-asset based on the applicable IAS and found that the most common treatment for Crypto asset is as Intangible Asset and Inventory since the used of Crypto-Asset until now mostly as investment and trading in contract futures.…”
Section: Audit Of Crypto Currency Transactionsmentioning
confidence: 99%